â€œInfluence Analysis of Per Capita Income, Minimum Wages and Education Levels On Labor Supply Of Young Age In Indonesiaâ€ - B01112024, Egi Ilmar Anugrah (Jurnal Pembangunan dan Pemerataan, 2016)
The research objective is to determine and analyze the per capita income, minimum wages and education levels affect the labor supply of young age in Indonesia. Data analysis techniques used in this research is multiple linear regression with the data processing program Eviews 8. The results showed that the independent variables per capita income is not significant positive effect on labor supply young age, minimum wage significant negative effect on labor supply of young age and education level significant negative effect on labor supply young age. Simultaneously to three independent variables have a significant effect on labor supply young age.Keywords : Labor Supply, Per Capita Income, Minimum Wages, Education Levelâ€œAnalisis Pengaruh Pendapatan Per Kapita, Upah Minimum, dan Tingkat Pendidikan Terhadap Penawaran Tenaga Kerja Usia Muda Di Indonesiaâ€